Study on the abrasion property of the anvil inside a hydraulic DTH hammer fitted with horizontal oriented sliders - Jiang-fu He; Qi-lei Yin; Kun Yin (Fracture and Structural Integrity)
Hydraulic hammers have been extensively applied to horizontal directional well drilling in hard rock formations. However, the service life of a hydraulic hammer is still unsatisfactory due to the heavy wear or abrasion of the horizontal anvil, which leads to the failure and the reduction of service life in directional well drilling. In order to improve the performance life of a hydraulic hammer, the new type of anvil with a horizontal oriented slider has been designed. The abrasion property of the horizontal oriented slider have been numerically simulated and analyzed by Finite Element Analysis. Simulation and experimental results have shown that the abrasion rate exponentially varies with the mass of the anvil and the friction coefficient of horizontal oriented slider, nevertheless the abrasion rate of horizontal anvil is almost logarithmically varies with moving velocity of oriented slider. The maximum abrasion rate of horizontal oriented sliders will exceed 4% while moving velocity of the horizontal anvil is larger than 3m/s. While the mass of the anvil is 100kg, the maximum abrasion rate of horizontal oriented slider is 7.5?. However, the maximum abrasion rate of a horizontal oriented slider will be up to 16.5% while the friction coefficient is more than 0.2.